Inquiry Based Teaching in Writing Classroom: the Effectiveness to the Students’ Creativity - Fitria Wulan Sari (Journal of English Language Teaching and Islamic Integration, 2020)
The main objectives of the research are to find out whether (1) Inquiry Based Teaching is more effective than Guided Writing to teach  writing  skill;  (2)  Students  having  high  creativity  have  better writing  skill  than  those  having  low  creativity;  and  (3)  there  is  any interaction  between  teaching  methods  and  students’  creativity  in teaching  writing  skill  for  students.  The  research  applied  in  this research  was  an  experimental  research.  The  teaching  methods  are Inquiry  Based  Teaching  and  Guided  Writing.  Creativity  as  the attributive variable was divided into high creativity and low creativity. The population of the research was the students of junior high school consisting of 176 students. The samples of this research were the class 8B as experimental class and 8A as control class that consisted of 22 students  in  each  class.  The  result  of  data  analysis  shows  that;  (1) Inquiry  Based  Teaching  is  more  effective  than  Guided  Writing  to teach  writing  skill;  (2)  Students  having  high  creativity  have  better writing  skill  than  those  having  low  creativity;  and  (3)  There  is  an interaction between teaching methods and students’ creativity to teach writing skill for the students. Based on the research findings, it can be concluded that Inquiry Based Teaching is an effective method to teach writing  skill,  and  the  effectiveness  is  affected  by  the  degree  of students’ creativity .